Bridging Boundaries: Enhancing Visual Inquiry Tools for Ecosystems through Design Archaeology - Vorbohle, Christian (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))
Joint value creation of organizations in ecosystems have a high failure rate, stressing the need for tools that enable the alignment of business models through visual inquiry. However, existing visual inquiry tools rarely consider recent design knowledge or ecosystem understanding. This leads to dissatisfied users and impedes the full realization of ecosystems’ potential. This short paper proposes an archaeological design science approach for enhancing the design of visual inquiry tools (e.g., a canvas) for ecosystems. Preliminary findings reveal 24 relevant artifacts, and shortcomings in the creation of conceptual models and rigorous evaluations. The proposed research process aims to develop design principles for more effective tools to bridge the gap between visual inquiry tools and ecosystems. This research contributes to design science research by reutilizing design knowledge and further developing the archaeological design approach. It also offers valuable information to practitioners about existing business model tools for the creation of ecosystems.
Keywords: Design Science Research; Design Archaeology; Canvas Analysis; Business Model Tools

Interview Study on Strategy Options for Platform Operation in B2B Markets - Özcan, Leon; Fichtler, Timm; Kasten, Benjamin; Koldewey, Christian; Dumitrescu, Roman
Keywords: Digital Platform; Platform Strategy; Strategic Management; Platform Life Cycle; Interview Study; Business Model; Business-to-Business; Two-sided Market; Multi-sided Market

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development

Supporting Business Model Generation with Augmented Reality - Gräßler, Iris; Grewe, Benedikt; Kramer, Hendrik; Pottebaum, Jens (LUT Scientific and Expertise Publications)
Workshops on business model generation lead to collaborative work phases and discussions on business models. Therefore, tools such as the Business Model Canvas are used, typically filled with sticky notes. Generated content needs to be digitized in a time-consuming manual follow-up as part of the documentation and basis for a further use of the results in the company. In addition, there are challenges, such as decentralized work and digital workshop formats. Augmented Reality offers a way to reduce the digitization effort and enables decentralized work. In this research, the potentials of the use of AR technology in workshops on business model generation is investigated. Therefore, functions are implemented and evaluated in a demonstrator that reduces digitization effort and enable distributed work.
Keywords: business model generation; augmented reality; workshop; collaborative work; digitization; AR-supported workshop concept; immersive technologies; decentralized work; business model canvas

Situation-specific Business Model Development Methods for Mobile App Developers - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Enterprise, Business-Process and Information Systems Modeling)
The development of effective business models is an essential task in highly competitive markets like mobile ecosystems. Existing development methods for these business models do not specifically focus that the development process profoundly depends on the situation (e.g., market size, regulations) of the mobile app developer. Here, a mismatch between method and situation can lead to poor resource management and longer development cycles. In software engineering, situational method engineering is used for software projects to configure a development method out of a method repository based on the project situation. Analogously, we support creating situation-specific business model development methods with a method base and new user roles. Here, the method engineer obtains the knowledge of the domain expert and stores it in the method base as elements, building blocks, and patterns. The expert knowledge is derived from a grey literature review on mobile development processes. After this, the method engineer constructs the development method based on the described situation of the business developer. We provide an open-source tool and evaluate it by constructing a local event platform's business model development method.
Keywords: Business Model Development; Situational Method Engineering; Mobile App; Business Model Development Tools

Situation- and Domain-specific Composition and Enactment of Business Model Development Methods - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Product-focused Software Process Improvement)
Developing effective business models is a complex process for a company where several tasks (e.g., conduct customer interviews) need to be accomplished, and decisions (e.g., advertisement as a revenue stream) must be made. Here, domain experts can guide the choices of tasks and decisions with their knowledge. Nevertheless, this knowledge needs to match the situation of the company (e.g., financial resources) and the application domain of the product/service (e.g., mobile app) to reduce the risk of developing ineffective business models with low market penetration. This is not covered by one-size-fits-all development methods without tailoring before the enaction. Therefore, we conduct a design science study to create a situation-specific development approach for business models. Based on situational method engineering and our previous work in storing knowledge of methods and models in distinct repositories, this paper shows the situation-specific composition and enaction of business model development methods. First, the method engineer composes the development method out of both repositories based on the situational context. Second, the business developer enacts the method and develops the business model. We implement the approach in a tool and evaluate it with a industrial case study on mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Lean Development; Kanban Boards; Canvas Models

Hypothesis-driven Adaptation of Business Models based on Product Line Engineering - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Proceedings of the 22nd IEEE International Conference on Business Informatics)
The continuous innovation of its business models is an important task for a company to stay competitive. During this process, the company has to validate various hypotheses about its business models by adapting to uncertain and changing customer needs effectively and efficiently. This adaptation, in turn, can be supported by the concept of Software Product Lines (SPLs). SPLs reduce the time to market by deriving products for customers with changing requirements using a common set of features, structured as a feature model. Analogously, we support the process of business model adaptation by applying the engineering process of SPLs to the structure of the Business Model Canvas (BMC). We call this concept a Business Model Decision Line (BMDL). The BMDL matches business domain knowledge in the form of a feature model with customer needs to derive hypotheses about the business model together with experiments for validation. Our approach is effective by providing a comprehensive overview of possible business model adaptations and efficient by reusing experiments for different hypotheses. We implement our approach in a tool and illustrate the usefulness with an example of developing business models for a mobile application.
Keywords: Business Model Decision Line; Business Model Adaptation; Hypothesis-driven Adaptation; Software Product Line; Feature Model

Model-based Hypothesis Engineering for Supporting Adaptation to Uncertain Customer Needs - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Business Modeling and Software Design)
To build successful products, the developers have to adapt their product features and business models to uncertain customer needs. This adaptation is part of the research discipline of Hypotheses Engineering (HE) where customer needs can be seen as hypotheses that need to be tested iteratively by conducting experiments together with the customer. So far, modeling support and associated traceability of this iterative process are missing. Both, in turn, are important to document the adaptation to the customer needs and identify experiments that provide most evidence to the customer needs. To target this issue, we introduce a model-based HE approach with a twofold contribution: First, we develop a modeling language that models hypotheses and experiments as interrelated hierarchies together with a mapping between them. While the hypotheses are labeled with a score level of their current evidence, the experiments are labeled with a score level of maximum evidence that can be achieved during conduction. Second, we provide an iterative process to determine experiments that offer the most evidence improvement to the modeled hypotheses. We illustrate the usefulness of the approach with an example of testing the business model of a mobile application.
Keywords: Hypothesis Engineering; Model-based; Customer Need Adaptation; Business Model; Product Features

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Intertwined Development of Business Model and Product Functions for Mobile Applications: A Twin Peak Feature Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Software Business)
Mobile app stores like Apple's AppStore or Google's PlayStore are highly competitive markets for third-party developers wanting to develop successful applications. During the development process, many developers focus on the multitude of product functions but neglect the business model as an equally important part. As a result, developers often fail to meet customer needs, leading to unnecessary development costs and poor market penetration. This, in turn, raises the question of how we intertwine the business model and product functions during the development process to ensure a better alignment between the two. In this paper, we show this intertwined development by adapting the concept of Twin Peaks to the business model and product functions. Based on feature modeling as an abstraction layer, we introduce the concept of a Business Model Decision Line (BMDL) to structure the business model decisions and their relation to product functions structured in a Software Product Line (SPL). The basis of our feature models is the analysis of top listed applications in the app stores of Apple and Google. To create and modify both models, we provide an incremental feature structuring and iterative feature selection process. This combination of abstraction layer and development process supports third-party developers to build successful applications both from a business and a product perspective.
Keywords: Intertwined Development; Twin Peaks; Feature Model; Business Model; Product Functions